Experiences of National Disability Insurance Scheme planning from the perspective of adults with intellectual disability - Perry, E.; Waters, Rebecca; Buchanan, Angus (WILEY, 2019)
The Australian National Disability Insurance Scheme (NDIS) is attempting to address long-term inequalities experienced by people with disability. Planning is central to the NDIS. People with intellectual disability will be the largest group of NDIS participants, and their perspectives are underrepresented in the literature. It is important to understand how they experience and perceive NDIS planning. Ten adults with intellectual disability participated in semi-structured interviews to explore their experiences of NDIS planning. Data were analysed using Braun and Clarke's (2006, Qualitative Research in Psychology, 3, 77) six stages of thematic analysis. Six themes were identified: planning preparation not fit for purpose, creating goals, goals not met, planning not meeting real needs, lack of choice and control and importance of relationship with planner. In principle, the NDIS presents a real opportunity to increase the choice and control, social and economic participation, and independence of people with disability; however, this does not always translate into practice for people with intellectual disability.